Comparison of NAA XRF and ICP-OES Methods on Analysis of Heavy Metals in Coals and Combustion Residues - Agus Taftazani; Roto Roto; Novitasari Restu Ananda; Sri Murniasih (Indonesian Journal of Chemistry, 2017)
Heavy metals in the samples of coals and combustion residues (bottom ash and fly ash) from Pacitan coal-fired power plant (CPP) have been identified by using NAA, XRF, and ICP-OES methods. This research was aimed to understand the analysis results correlation coefficient (R) and determine the enrichment ratio (ER) value of the samples by using three analysis methods. The results showed 10 elements have been simultaneously detected in all samples. The correlation coefficient of analysis results of metals content in coals by using NAA-XRF, XRF-ICP OES and with ICPOES-NAA methods gives R2£1 respectively. The correlation coefficient of analysis results of metals content in bottom ash and fly ash by using the methods of NAA-XRF, XRF-ICPOES, and ICPOES-NAA gained R2»1 respectively. ICP-OES method was most satisfactory in this study. The value of ER for identified metals by using the three methods in the samples of bottom ash and fly ash yielded the value over one, and ER value of fly ash was greater in comparison to the bottom ash.